Tachlīl al-Khuththah ad-Dirāsiyyah li Māddati ‘Ilmi al-Ashwat fī al-Jāmi’āt al-Indūnīsiyyah fī Dhau`i Kitab “al-Idhā`āt” li ‘Abd ar-Rahmān al-Fauzān - Lubis, Torkis (Universitas Negeri Malang, 2023)
In this study, the researcher analyzed the curriculum for the Phonetics course in four Indonesian universities considering the book